2022
DOI: 10.1186/s11658-022-00359-z
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic utility of mesenchymal stromal cell (MSC)-based approaches in chronic neurodegeneration: a glimpse into underlying mechanisms, current status, and prospects

Abstract: Recently, mesenchymal stromal cell (MSC)-based therapy has become an appreciated therapeutic approach in the context of neurodegenerative disease therapy. Accordingly, a myriad of studies in animal models and also some clinical trials have evinced the safety, feasibility, and efficacy of MSC transplantation in neurodegenerative conditions, most importantly in Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), and Huntington’s disease (HD). The MSC-mediated desired effect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 207 publications
0
14
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs)-derived extracellular vesicles (EVs) have been reported to show potent anti-inflammatory effects in a variety of diseases such as osteoarthritis, cardiovascular diseases, graft-versus-host disease (GVHD), and neurodegenerative diseases [ 1 – 5 ]. As nanoscale non-reproducible lipid bilayer particles, EVs are naturally released by most, if not all, types of cells and are present in most bodily fluids [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs)-derived extracellular vesicles (EVs) have been reported to show potent anti-inflammatory effects in a variety of diseases such as osteoarthritis, cardiovascular diseases, graft-versus-host disease (GVHD), and neurodegenerative diseases [ 1 – 5 ]. As nanoscale non-reproducible lipid bilayer particles, EVs are naturally released by most, if not all, types of cells and are present in most bodily fluids [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…MSCS can be considered as mini-bioreactors capable of secreting a wide range of cytokines and neurotrophic factors that are crucial in the treatment of neurodegenerative disorders. There is a substantial body of evidence that MSCs express a variety of neurotrophic factors, including nerve growth factor, GDNF, BDNF, insulin-like growth factor-1, and basic fibroblast growth factor at both the mRNA and protein levels [68][69][70]. Synaptic plasticity, as well as the survival and function of midbrain dopamine neurones, are dependent on BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…8a and b). Neurotrophic factors, such as BDNF and GDNF, are crucial for the synaptic activity, survival, and function of DA neurones, and their decline has been linked to motor deficits associated with aged animals [68][69][70][71][72][73][74][75]. In the striatum of aged rats, the expression of BDNF, GDNF, and VEGF was remarkably reduced when compared with the expression in control rats, and these declines were reversed by BMMSC transplantation (Fig.…”
Section: Bmmscs Induced Antioxidative Effects and Restored Neurotroph...mentioning
confidence: 94%
“…In addition, we also found that ectopic expression of KAT7 also up-regulated P15, indicating that p15 acts downstream of KAT7 in mediating cellular sensitivity. Of course, the anti-aging mechanism of β-carotene needs further in-depth research in the future, because MSC senescence is a very complex biological process [ 28 32 ].…”
Section: Discussionmentioning
confidence: 99%